(untitled) (Journal of Partial Differential Equations, 2002)
This paper deals with the long time behavior of solutions for the dissipative generalized symmetric regularized long wave equations. We show the existence of global weak attractors for the periodic initial value problem of the equations in H¹ × L². The finite dimensionality of the global attractors is also established.